Chernysh A. Destructive forms of reception posttotalitarian discourse in thenovel of S. Protsiuk «Infection» - Chernysh A. (Philological Treatises, 2020)
The article is devoted to the identification of destructive forms of perceiving the world by the characters of the novel S. Protsiuk «Infection», a mental formation which occurred in the Soviet and postsoviet periods. The article is dedicated to the mental problems of development of posttotalitarian reality, marked by posttotalitarian trauma, the experience of the eradication of the colonial ideology, the change of moral and cultural imperatives that define the nature of the psychological formation of identity and self-presentation of the characters in the novel. The article reveals psychological causes of destructive behavior of the characters, as well as forms of reception and assimilation of posttotalitarian discourse. Reveals the locus of Kyiv city as a space of opportunism, immorality, immorality that destructure mental nature of most of the characters.